Effect of particle strength on the monotonic shear strength of clinker ash. Issue 3 (18th September 2013) - Hyodo, M; Nakashita, A; Ohara, N; Nakata, Y; Yoshimoto, N; Yoshioka, I; Winter, M
Abstract : Particle crushing tests were performed on single particles from six types of clinker ash, as well as a series of monotonic shear tests using effective confining pressures σ' c of 50, 100 and 200 kPa at an intended degree of compaction D c = 100%, in order to investigate the relationship between particle strength and monotonic shear strength. Samples with intended degrees of compaction D c = 85% and 90% were also tested at σ' c = 50 and 100 kPa in order to investigate the effect of degree of compaction on the shear strength of clinker ash. It was found that clinker ash is a crushable material with weak particle strength when compared with natural sands, although it has higher shear strength especially at D c ≥ 95%, where the shear resistance angle exceeds 45°. The average crushing stress σ f of the particles shows a strong correlation with the residual secant friction angle ϕ res, with ϕ res increasing along with the average crushing stress σ f . It was also found that σf can be used to calculate ϕ res and, in turn, the peak secant friction angle ϕ peak of clinker ash.